Eyob Ghebreziabhier Bein, Tigriyna Dictionary, I: Tigriyna–Italian– English: Modern Dictionary, II: Italian–Tigriyna–English: Modern Dictionary, III: English–Tigriyna–Italian: Modern Dictionary - Voigt, Rainer (Aethiopica, 2018)
Review